Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1158/1538-7445.am2016-2296
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2296: Inhibition of the PI3K/Akt pathway during CAR T cell production results in enhanced efficacy across multiple in vivo tumor models

Abstract: Patients treated with chimeric antigen receptor (CAR) T cells targeting CD19 for B cell malignancies have experienced rapid and durable tumor regressions. Manufacture of CAR T cells for treatment requires ex vivo culture to facilitate CAR gene transfer and to achieve a therapeutic dose of the modified cells. Recent data suggests that specific T cell subtypes can provide enhanced anti-tumor efficacy, spurring efforts to optimize the production of therapeutic T cells via the cumbersome physical isolation of cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While demonstrated to be effective in the treatment of a number of malignancies, the presence of IL-2 within ex vivo cultures, necessary to maintain viability, has, paradoxically been shown to reduce CAR T cell activity [99]. Similarly, it was recently demonstrated that the efficacy of CAR T cells in the treatment of solid tumours in vivo, could be improved with the addition of PI3K inhibitors during ex vivo culturing, however, these were preliminary findings and the underlying mechanism remains to be fully elucidated [99,100].…”
Section: Combination With Immunotherapiesmentioning
confidence: 99%
“…While demonstrated to be effective in the treatment of a number of malignancies, the presence of IL-2 within ex vivo cultures, necessary to maintain viability, has, paradoxically been shown to reduce CAR T cell activity [99]. Similarly, it was recently demonstrated that the efficacy of CAR T cells in the treatment of solid tumours in vivo, could be improved with the addition of PI3K inhibitors during ex vivo culturing, however, these were preliminary findings and the underlying mechanism remains to be fully elucidated [99,100].…”
Section: Combination With Immunotherapiesmentioning
confidence: 99%